Prescribing in primary care in a rural population in the Faro district - Medeiros, Armando De (2000)
Objectives: 1. To characterise medical prescription in primary health care for a rural population of the Faro district. 2. To characterise the type of systemic antibiotics prescribed, as well as the reasons for encounter and diagnoses leading to their prescription. Methods: Cross-sectional, descriptive study carried out in two rural counties in the Faro district. Variables (age, sex, type of encounter, reason for encounter, diagnosis, and drug therapy) were recorded and coded by using ICPC and the ICPC Classification of Drugs. Data were collected for three consecutive months as a convenience sample. Results: 1.5 drugs per office visit were prescribed; 77% of encounters included drug prescription; 15.5% of de novo diagnoses did not lead to any kind of drug prescription; the most frequently prescribed anatomical drug group was that of the cardiovascular system - 24% of total medication; the most frequently prescribed chemical groups were NSAIDs (8.2%) and benzodiazepines (5.6%). In this study, one antibiotic was prescribed for every 13 consultations, 41% of which being penicillin or derivatives. The diagnoses which more often led to antibiotic therapy belonged to the Respiratory and Urology Chapters. The most frequently prescribed chemical group of antibiotics was that of penicillins (-lactamase sensitive). Discussion: In this study some of the results obtained were similar to those found in the literature, especially concerning the proportion of clinical encounters leading to prescription of medicines, as well as the more prescribed chemical groups. However, antibiotic prescription seemed to be more diversified than shown by trends in other countries